Justifying transgression : Muslims, Christians, and the law, 1200 to 1700 - Kruijtzer, Gijs (De Gruyter, 2024)
"How do people justify what others see as transgression? Taking that question to the Persian-Muslim and Latin-Christian worlds over the period 1200 to 1700, this book shows that people in both these worlds invested considerable energy in worrying, debating, and writing about proscribed practices. It compares how people in the two worlds came to terms with the proscriptions of sodomy, idolatry, and usury. When historians speak of the gap between premodern practice and the legal theory of the time, they tend to ignore the myriad of justifications that filled this gap. Moreover, a focus on justification evens out many of the contrasts that have been alleged to exist between the two worlds, or the Muslim and Christian worlds more generally. The similarities outweigh the differences in the ways people came to terms with the various rules of divine law. The level of flexibility of the theologians and jurists in charge of divine law varied more over time and by topic than between the two worlds. Both worlds also saw the development of ever more sophisticated justifications. Amid the increasing complexity of justifications, a particular kind of reasoning emerged: that good outcomes are more important than upholding rules for their own sake"--Publisher's description.